(untitled) (Revista Educação, Artes e Inclusão, 2021)
This article is the result of research on the field of analysis of deaf student interaction, carried out in the premises of two public schools: the first elementary school, located near the city center of Criciúma - SC, and the other, high school, located in the center of Criciuma - SC. For data collection, observations and interviews were made with deaf students, in addition to the application of questionnaires to listening and interpreting teachers, in order to evaluate the quality of deaf education from the pedagogical perspective. In general this article also presents the professionals who are involved with deaf education, as is the case of the regular class teacher with deaf included, who may represent varied interpretations, according to the different cultures and social differences represented in class; In addition to the presence of the interpreter of Libras that represents the bridge of communication, but that education does not rely on this professional to avoid the effort that must be collective. The methodology used in this research was the field research with questionnaires applied to the research participants, besides consulting the references of the area, such as Perlin (1998), Skliar (1998), Goldfeld (2002), among others.